Preliminary efficacy of AWARE in college health service centers: A group psychotherapy intervention for Asian American women. Issue 3 (3rd April 2022) - Hahm, Hyeouk Chris; Hsi, Jenny H.; Petersen, Julie M.; Xu, Jiaman; Lee, Eunmyoung A.; Chen, Stephen H.; Liu, Cindy H.
Abstract: Objective Asian Women's Action for Resilience and Empowerment (AWARE) is a psychotherapy intervention designed to improve the mental health of Asian American women. This study documented the feasibility and preliminary efficacy of AWARE at three university health service centers in Massachusetts. Participants : 174 female Asian American college/graduate students were screened, and 48 (64%) met the eligibility criteria and enrolled in the study. Methods : This study was a non-randomized, pre-post design at three university/college health service centers in Massachusetts. Retention rates and changes in depression, anxiety, and PTSD symptoms were measured. Results : Results demonstrated high feasibility and significant preliminary efficacy of AWARE across the sites. After the completion of AWARE, participants showed statistically and clinically significant reduction of depression, anxiety, and PTSD symptoms ( p- values <.001). Conclusions : This study provides strong evidence that AWARE can be successfully implemented in university settings and provides a promising model of mental health treatment for Asian American women.